Free Vascularized Medial Femoral Condyle Bone Graft After Failed Scaphoid Nonunion Surgery. (15th August 2018) - Pulos, Nicholas; Kollitz, Kathleen M.; Bishop, Allen T.; Shin, Alexander Y.
Abstract : Background: Outcomes following revision surgery for scaphoid nonunions with osteonecrosis are guarded. We hypothesized that use of free vascularized medial femoral condyle (MFC) bone grafts can lead to healing of the nonunion, increase vascularity of the proximal pole, and restore scaphoid architecture, resulting in acceptable functional outcomes. Methods: We performed a retrospective review of 49 patients who were treated with an MFC bone graft, between May 2005 and September 2016, after prior failure of operative treatment for scaphoid nonunion. The mean time from the injury to the revision surgery with the MFC bone graft was 24 months, and the mean time from the prior, failed surgery was 15 months. Thirty-six of the 49 patients had had a prior bone graft procedure and 6 patients had had 2 previous surgical procedures for the nonunion. The initial internal fixation of the scaphoid fracture was with a scaphoid screw in 43 patients. All patients had documented osteonecrosis of the proximal pole at the time of our surgery. Carpal indices, time to union, pain scores, functional outcomes, and complications were recorded. Results: Forty-one (84%) of the 49 previously operated on scaphoid nonunions healed at a mean of 16 weeks (range, 9 to 31 weeks) after the MFC bone-grafting as confirmed on computed tomography (CT). Radiographs demonstrated significant improvement in carpal alignment following the surgery with the MFC bone graft. Comparison between preoperative and postoperative values showed a trend toward improved grip strength and no important change in total wrist range of motion. Subsequent procedures were performed in 29 patients, 21 of whom had planned Kirschner wire removal. All 24 patients in whom scaphoid union had been achieved and who were available for follow-up were able to work or attend school full-time, and 88% were satisfied or very satisfied with their wrist function. Age, smoking status, body mass index, time to surgery, and preoperative radiographic findings were not found to be significant predictors of failure. Conclusions: MFC grafts increase vascularity and restore scaphoid architecture, promoting union in most patients with the combination of proximal pole osteonecrosis, carpal collapse, and failed prior scaphoid nonunion surgery. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.